A power saving jamming system for E-GSM900 and DCS1800 cellular phone networks for search and rescue applications - Zorn, Stefan; Maser, Matthias; Götz, Alexander; Rose, Richard; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2011)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the German Federal Ministry of Education and Research. In this project partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. To locate a person by his or her mobile phone requires to take over the phone by an own Base Transceiver Station (BTS). Jamming all other networks is one option to achieve that. This paper will introduce a new Field Programmable Gate Array (FPGA) based jamming system which consumes little power and disturbs only small parts of the GSM spectrum but reliably cuts all connections between mobile stations (MS) and existing BTS.
elib2cris::1512001600,zorn2011